OR26-5 Functional Analysis of Estrogen-Regulated Enhancer RNAs in Breast Cancer Cells - Hou, Tim (J Endocr Soc, 2019)
Approximately 70% of breast cancers express estrogen receptor alpha (ERα), a hormone-regulated transcription factor, making it an excellent target for endocrine therapy. When endogenous and exogenous ligands engage ERα, the receptor binds to regulatory regions in the genome known as enhancers, where it associates with coregulatory proteins, increases histone modifications associated with active enhancers, promotes chromatin looping, stimulates enhancer transcription and the production of enhancer RNAs (eRNAs), and ultimately regulates target gene transcription. We have previously used global run-on sequencing (GRO-seq), a high-throughput method that identifies the location and orientation of all transcriptionally active RNA polymerases across the genome, to identify active enhancers based on enhancer transcription and enrichment of the aforementioned genomic features. Current studies on the roles of eRNAs have suggested that eRNAs may 1) recruit regulatory proteins to enhancers; 2) promote RNA polymerase II transition; 3) regulate histone modification; and 4) increase chromosome looping. One challenge facing the field is the lack of accurate eRNA annotations and cloned full-length eRNAs; eRNAs have typically been studied as signals from genomic assays on ‘browser tracks,’ not as physical entities (e.g., cDNAs). We have employed precision nuclear run-on of capped RNA (PRO-cap) to determine the transcription start sites of all expressed eRNAs. In addition, we have also used ultra-deep RNA-sequencing of polyA-depleted and polyA-enriched RNA fractions to detect eRNAs and examine for the potential splicing of eRNAs. Combining these genomic data, our annotations provide critical information for the large-scale cloning of eRNAs. We are now testing whether eRNAs originating from ERα enhancers may regulate target gene expression, either in cis or in trans. We cloning specific eRNAs based on our genomic annotations and testing them either by (1) tethering them to their cognate ERα enhancers by using CRISPR/dCas9 technology (i.e., cis) or (2) ectopically expressing them (i.e., trans) in MCF-7 breast cancer cells. Ultimately, our genomic annotation and biochemical tools will allow us to determine the mechanisms by which eRNA contribute to ERα enhancer assembly and function. This work is supported by grants from the NIH/NIDDK (DK058110) and CPRIT (RP160319) to W.L.K.